Main bacterial species causing clinical disease in ornamental freshwater fish in Brazil - Cardoso, Pedro H M; Moreno, Luisa Z; de Oliveira, Carolina H; Gomes, Vasco T M; Silva, Ana Paula S; Barbosa, Mikaela R F; Sato, Maria Inês Z; Balian, Simone C; Moreno, Andrea M (Folia microbiologica, 2021)
Bacterial diseases are common in ornamental fish, more frequently associated with ubiquitous bacteria from the aquarium environment. The disease can lead to fish mortality and cause high economic losses if not rapidly controlled. The aim of this study was to identify the main causative bacterial agents of infection in ornamental fish with different clinical signs. A total of 126 freshwater fish, from 12 families and 38 species, with clinical signs were collected in a wholesaler in São Paulo, SP, Brazil. Samples were taken from the eye, skin ulcers, kidneys, and gills, plated on MacConkey, CHROMagar Orientation, and blood agar and incubated under aerobic and anaerobic conditions. Bacterial identification was performed by MALDI-TOF mass spectrometry. From the 126 studied animals, 112 were positive for bacterial isolation. Among the positive animals, 32.1% presented infection caused by a single bacterial species, while in the remaining 67.9%, two to six different bacterial species were identified. A total of 259 bacterial strains were obtained and classified among 46 bacterial species. The species of higher frequency were Aeromonas veronii (26.3%), Aeromonas hydrophilla (16.2%), Shewanella putrefaciens (7.3%), Citrobacter freundii (8.1%), Vibrio albensis (5.8%), and Klebsiella pneumoniae (4.2%). MALDI-TOF MS showed to be a rapid method for diagnosis of bacterial disease outbreaks in ornamental fish establishments.
Keywords: Brazílie; Animals; Fresh Water; Humans; nemoci ryb; Fish disease; lidé; zvířata; Fish Diseases; Fishes; Bacterial disease; Aeromonas; sladká voda; Animal health; Brazil; Diagnosis in fish; ryby